The Neurophysiological Processing of Music in Children: A Systematic Review With Narrative Synthesis and Considerations for Clinical Practice in Music Therapy - Bower, Janeen; Magee, Wendy L.; Catroppa, Cathy; Baker, Felicity Anne (Frontiers in Psychology, 2021)
Introduction: Evidence supporting the use of music interventions to maximize arousal and awareness in adults presenting with a disorder of consciousness continues to grow. However, the brain of a child is not simply small adult brain, and therefore adult theories are not directly translatable to the pediatric population. The present study aims to synthesize brain imaging data about the neural processing of music in children aged 0-18 years, to form a theoretical basis for music interventions with children presenting with a disorder of consciousness following acquired brain injury. Methods: We conducted a systematic review with narrative synthesis utilising an adaptation of the methodology developed by Popay et al (2006). Following the development of the narrative that answered the central question ‘What does brain imaging data reveal about the receptive processing of music in children?’, discussion was centred around the clinical implications of music therapy with children following acquired brain injury. Results: The narrative synthesis included 46 studies that utilized EEG, MEG, fMRI and fNIRS scanning techniques in children aged 0-18 years. From birth, musical stimuli elicit distinct but immature electrical responses, with components of the auditory evoked response having longer latencies and variable amplitudes compared to their adult counterparts. Hemodynamic responses are observed throughout cortical and subcortical structures however cortical immaturity impacts musical processing and localization of function in infants and young children. The processing of complex musical stimuli continues to mature into late adolescence. Conclusion: While the ability to process fundamental musical elements is present from birth, infants and children process music more slowly and utilize different cortical areas compared to adults. Brain injury in childhood occurs in a period of rapid development and the ability to process music following brain injury will likely depend on pre-morbid musical processing. Further a significant brain injury may disrupt the developmental trajectory of complex music processing. However, complex music processing may emerge earlier than comparative language processing, and occur throughout a more global circuitry.